Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1177/2042018819871166
|View full text |Cite
|
Sign up to set email alerts
|

Health considerations for transgender women and remaining unknowns: a narrative review

Abstract: Transgender (trans) women (TW) were assigned male at birth but have a female gender identity or gender expression. The literature on management and health outcomes of TW has grown recently with more publication of research. This has coincided with increasing awareness of gender diversity as communities around the world identify and address health disparities among trans people. In this narrative review, we aim to comprehensively summarize health considerations for TW and identify TW-related research areas that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 230 publications
0
41
0
3
Order By: Relevance
“…In Malaysia, based on the data from Integrated Biological and Behavioural Surveillance studies showed increment from 4.8% -12.4% of transgender women were HIV positive, with higher estimation among those who engaged in sex work (Rutledge et al, 2018). HIV transmission risk in transgender women increases with various exposures such as violence victimization, polysubstance use, depression, frequent alcohol use, multiple partners, lack of knowledge in HIV/AIDS, negative attitude towards HIV/AIDS, transactional sex and history of sex with adults before the age of 18 years (Gibson et al, 2016;Samsul D et al, 2016;Iwamoto et al, 2019). Transactional sex or known as survival sex (sex in exchange for money), had been the main risk of HIV as they are at greater risk for engaging in unprotected receptive anal sex (condomless), which usually motivated by high payment (Parsons et al, 2018;Baral et al, 2013;Shan et al, 2018).…”
Section: Human Immunode Iciency Virus (Hiv)mentioning
confidence: 99%
See 4 more Smart Citations
“…In Malaysia, based on the data from Integrated Biological and Behavioural Surveillance studies showed increment from 4.8% -12.4% of transgender women were HIV positive, with higher estimation among those who engaged in sex work (Rutledge et al, 2018). HIV transmission risk in transgender women increases with various exposures such as violence victimization, polysubstance use, depression, frequent alcohol use, multiple partners, lack of knowledge in HIV/AIDS, negative attitude towards HIV/AIDS, transactional sex and history of sex with adults before the age of 18 years (Gibson et al, 2016;Samsul D et al, 2016;Iwamoto et al, 2019). Transactional sex or known as survival sex (sex in exchange for money), had been the main risk of HIV as they are at greater risk for engaging in unprotected receptive anal sex (condomless), which usually motivated by high payment (Parsons et al, 2018;Baral et al, 2013;Shan et al, 2018).…”
Section: Human Immunode Iciency Virus (Hiv)mentioning
confidence: 99%
“…Despite the high prevalence of HIV among these community, they also contributed to low screening levels, most probably due to denial of having the illness (Gibson et al, 2016). HIV prevention, treatment and care should be priorities around the world, but these population experience many barriers to treatment ranging from incorrect pronoun use of their name, judgmental and insensitive statements, unwillingness to provide care, asked to change their appearance or felt they had to present as male to receive proper care, societal stigmatization, a lack of knowledge by the healthcare about transgender needs and the refusal of many national health systems or health insurance providers to cover their care (Gupta et al, 2016;Vijay et al, 2018;Iwamoto et al, 2019).…”
Section: Human Immunode Iciency Virus (Hiv)mentioning
confidence: 99%
See 3 more Smart Citations